Physical Properties of Unaged and Short-Term Aged (STA) Liquid Epoxidized Natural Rubber (LENR) Modified Binders - Roslan, Nor'Yuhanis; Mohd Kamaruddin, Nurul Hidayah; Mohd Yunus, Khairul Nizam; Poharan, Azuan; Hermadi, Madi; Yusof, Nurul Hayati; Mustafa Kamal, Mazlina (International Journal of Integrated Engineering, 2025)
Polymer-modified asphalt (PMA) binders have been utilized extensively to improve the performance and durability of asphalt pavement. Each type of polymer or modifier leads for specific alterations in the performance of the asphalt binder. This study examines how the physical properties of 60/70 penetration grade asphalt binder are influenced by the presence of liquid epoxidized natural rubber (LENR). Specifically, five different proportions of LENR were examined: 0%, 3%, 6%, 9%, and 12% by weight of the asphalt binder. A rolling thin film oven procedure was conducted to replicate the short-term aging of the asphalt binder samples. The unaged and short-term aged samples of LENR-modified asphalt binders were evaluated for physical testing  (penetration, softening point, and viscosity). The results show that with the increasing LENR, the penetration reduced, the softening point and viscosity increased. The findings in this study indicated that 3% LENR  showed good potential as modifier in asphalt binder.